2011
DOI: 10.1161/circulationaha.110.987263
|View full text |Cite
|
Sign up to set email alerts
|

Particle Traps Prevent Adverse Vascular and Prothrombotic Effects of Diesel Engine Exhaust Inhalation in Men

Abstract: Background-In controlled human exposure studies, diesel engine exhaust inhalation impairs vascular function and enhances thrombus formation. The aim of the present study was to establish whether an exhaust particle trap could prevent these adverse cardiovascular effects in men. Methods and Results-Nineteen healthy volunteers (mean age, 25Ϯ3 years) were exposed to filtered air and diesel exhaust in the presence or absence of a particle trap for 1 hour in a randomized, double-blind, 3-way crossover trial. Bilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
1
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(138 citation statements)
references
References 35 publications
6
124
1
7
Order By: Relevance
“…In a more recent study, no vascular impairment or effect on blood clotting were observed in volunteers exposed for 2 hours to 70 µg/m 3 of ultrafine carbon particles (Mills et al, 2011). In this same study, and in Lucking et al (2011), it was shown that removing the particles from diluted diesel engine exhaust also prevented adverse effects on the cardiovascular system. The difference is explained by the differences in composition, with black carbon particles (soot) being rich in (semi)volatile organic particles and metals.…”
Section: Clinical Studiesmentioning
confidence: 54%
See 2 more Smart Citations
“…In a more recent study, no vascular impairment or effect on blood clotting were observed in volunteers exposed for 2 hours to 70 µg/m 3 of ultrafine carbon particles (Mills et al, 2011). In this same study, and in Lucking et al (2011), it was shown that removing the particles from diluted diesel engine exhaust also prevented adverse effects on the cardiovascular system. The difference is explained by the differences in composition, with black carbon particles (soot) being rich in (semi)volatile organic particles and metals.…”
Section: Clinical Studiesmentioning
confidence: 54%
“…This is an important paper, as this result contrasts markedly with the group's previous findings using diesel exhaust containing high concentrations of NO 2 . A subsequent paper, examining the vascular and prothrombic effects of diesel exhaust (300 µg/m 3 for 1 hour), with and without inclusion of a particle trap, demonstrated that a reduction of particle number and mass concentration, in the absence of changes in nitrogen oxides, was associated with reduced adverse cardiovascular outcomes (Lucking et al, 2011). This was interpreted as strongly supporting the view that fine particles, and not NO 2 , were driving the previously reported cardiovascular effects, especially as NO 2 concentrations increased almost five-fold with the particle trap.…”
Section: Chamber Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[61][62][63] Several studies have linked air pollution to endothelial dysfunction. 64,65 In a mouse model, air pollution induced insulin resistance and endothelial dysfunction. 66 This effect was attributable to increased adipose tissue inflammation, which has been linked to the pathogenesis of diabetes mellitus.…”
Section: Mechanisms Of Endothelial Dysfunction: Human Studiesmentioning
confidence: 99%
“…This research demonstrates how interventions can make a real difference to cardiovascular health." 5 Professor Newby was also involved in another intervention study in 2008 examining the impact of the smoking ban in Scotland that also generated positive results. 6 The Study of Public Place Intervention on Tobacco Exposure (STOPIT), led by Professor Jill Pell, MD, FFPHM (see http://circ.ahajournals.org/content/120/6/f31), at the University of Glasgow, Glasgow, Scotland, found a 17% reduction in cases of myocardial infarction presenting to hospital after the smoking ban in public places came into force compared to before the ban.…”
mentioning
confidence: 99%